NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM FESTIVAL SEKALA BEKHAK DI LAMPUNG BARAT - Reni Susilawati; Nasor; Siti Zulaikhah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and describe the representation of Islamic Religious Education (PAI) values, encompassing the aspects of aqidah (creed), sharia (Islamic law), and akhlaq (morality), within the main processions of the Sekala Bekhak Festival in West Lampung Regency. The focus of the study is directed toward examining how local traditions such as Sekura, Gambus Orchestra, and Nyambai function as media for the internalization of religious values within the community. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through participatory observation of festival processions, in-depth interviews with tourism office officials, traditional leaders, religious leaders, and community figures, as well as documentation studies. Data validity was ensured through source triangulation, while data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the Sekala Bekhak Festival integrates aqidah values through symbols of the triumph of faith and devotional chants emphasizing monotheism. Sharia values are represented through adherence to modest dress codes in the Sekura performances and the regulation of social ethics (muamalah), while akhlaq values are manifested in the spirit of egalitarianism and the elimination of social barriers. The results further demonstrate that the festival has a significant impact on strengthening religious character and revitalizing social awareness within the community. The implications of this study highlight the importance of preserving religious-based cultural traditions as instruments of non-formal character education. The novelty of this research lies in its disclosure and analysis of the Islamic Religious Education dimension within the implementation of the Sekala Bekhak Festival, which encompasses the traditions of Sekura, Gambus, and Nyambai. Unlike previous studies that primarily emphasize historical and artistic aspects, this research specifically examines the integration of Islamic Religious Education values embedded in the Sekala Bekhak Festival.